Bird by bird with Annie [videorecording (DVD)] : a portrait of writer Anne Lamott - Lamott, Anne; Mock, Freida Lee (Docuramafilms : Distributed by New Video, 2009)
Offers an intimate portrait of the celebrated writer as well as her craft, interweaving the story of Lamott's life, in itself a deeply moving tale of addiction and redemption, grief and joy, intellect and faith, with one year's worth of interviews, public lectures, and readings, and footage of the writer at work.